Grass – woodland transitions : determinants and consequences for ecosystem functioning and provisioning of services - Sala, Osvaldo E; Maestre, Fernando T (Journal of Ecology, 2014)
1. A large fraction of grasslands world-wide is undergoing a rapid shift from herbaceous to woody- plant dominance, while in other parts of the world, the opposite transition from woodland to grassland is the dominant phenomenon. These shifts have received increasing attention in the ecological litera- ture during the last two decades due to their global extent and their impacts on ecosystem functioning. 2. This Special Feature includes a series of contributions on key topics within the study of grass– woodland transitions, including three articles addressing the drivers of these vegetation shifts and another three evaluating their ecological consequences. These articles, which include reviews, mod- elling and empirical studies, highlight the multiplicity of approaches and spatial scales being cur- rently used when studying grass–woodland transitions. 3. The first articles focus on the role of fire in driving the dynamics of mesic grasslands in the USA, on the effects of climate change on the transition zones between treeless vegetation, savanna and forest in tropical and subtropical Americas and on the role of the internal structure of vegetation as a determinant of grassland–woodland transitions. The articles devoted to exploring the conse- quences include a modelling study on the ecohydrological consequences of shrub removal in wes- tern North America and an empirical study aiming at understanding how abiotic and biotic attributes influence above-ground net productivity across Patagonian grasslands and shrublands, as well as a review of the consequences of brush management on the provision of ecosystem services. 4. Synthesis. Identifying the best actions to avoid or take advantage of grass–woodland transitions requires a mechanistic understanding of both the drivers of these shifts and their ecological conse- quences. The collection of reviews, empirical and modelling studies included in this Special Feature contributes to forecasting how ongoing global change will affect grass–woodland transitions and their consequences for the provisioning of ecosystem services from drylands, which account for a large fraction of Earth’s surface.
Keywords: climate change; ecosystem services; ecosystem–water dynamics; fire; Grasslands; inva- sion ecology; primary production; shrublands; vegetation shifts; woody-plant encroachment